Creep Deformation Behaviour and its Effect on Creep Life and Rupture Ductility of W-Mo-balanced 9Cr Steels. (3rd May 2020) - Abe, Fujio
ABSTRACT: The creep deformation behaviour and its effect on the creep life and rupture ductility are investigated for W-Mo-balanced 9Cr steels at 600 °C to 700 °C. The creep life is described as t r  = 1.5/[ ε ˙ min ( d ln ε ˙ /d ε )], where ε ˙ min and d ln ε ˙ /d ε reflect the creep deformation behaviour in the transient and acceleration creep regions, respectively. The creep life is also correlated with the time to minimum creep rate t m as t r  =  gt m, where g slightly increases with decreasing stress. The logarithm of creep rate linearly increases with strain in the initial stage of acceleration creep region. This is followed by a decrease in d ln ε ˙ d ε with strain at high stresses, resulting in ductile failure at large strains, while it is followed by an increase in d ln ε ˙ /d ε with strain at low stresses, resulting in rupture at small strains.